Developing a community-prioritized research agenda on primary care strategies for minimizing the health impacts of heat and poor air quality events: protocol - Gold, Rachel; Estiri, Hossein; Bunce, Arwen; McGrath, Brenda M.; Gunn, Rose; Steeves-Reece, Anna; Patel, Chirag J.; Pisciotta, Maura; George, Katie; Albright, Karen (Frontiers in Climate, 2026)
IntroductionExtreme heat / poor air quality events can adversely impact health, and low-income communities are especially vulnerable to these impacts. Evidence-based interventions that minimize these impacts are needed and ideally will be developed and led by front-line organizations such as primary care community health centers (CHCs). A community-driven and -prioritized research agenda is necessary to guide the generation of evidence that CHCs need to intervene effectively. We will generate this agenda via the following protocol.MethodsWe will first describe patterns of heat- and air quality-induced health impacts in a national CHC network (>2,400 clinics), focusing on hypertension and asthma. Results will be shared with advisors including: CHC staff and patients; representatives of community organizations focused on heat / air quality and health; and scientists with expertise in relevant fields. Advisors will identify additional needed analyses and consider potential interventions for interrupting the health impacts reflected in analysis results. Realist-informed qualitative data will be collected to identify likely mechanisms of effects of possible interventions. Using these inputs, we will identify a set of potential CHC-led interventions which will be categorized using a structured framework and then prioritized in terms of needed evidence on effectiveness, acceptability, and other factors. Several conceptual models guide this protocol.ResultsThis study began in Fall 2024, funded by the National Institutes of Health as a center planning grant. Quantitative analyses and qualitative data collection are underway, to be completed by Spring 2026; advisory committees will meet continuously through September 2027 to provide feedback, request additional analyses, generate potential interventions, and identify evidence needs and a related prioritized research agenda.DiscussionCHCs need evidence on: heat and air quality-induced health impacts in the populations they serve; how to intervene to minimize these impacts; and how to implement and sustain such interventions. Little prior research has identified or tested the effectiveness of such interventions in these settings. The process described here will create a research agenda on intervention effectiveness that reflects CHCs’ needs. It will be the first research agenda developed in partnership with CHC staff and patients, community organizations, and multidisciplinary scientists in the United States.